Association of Total Medication Burden With Intensive and Standard Blood Pressure Control and Clinical Outcomes: A Secondary Analysis of SPRINT. Issue 2 (August 2019) - Derington, Catherine G.; Gums, Tyler H.; Bress, Adam P.; Herrick, Jennifer S.; Greene, Tom H.; Moran, Andrew E.; Weintraub, William S.; Kronish, Ian M.; Morisky, Donald E.; Trinkley, Katy E.; Saseen, Joseph J.; Reynolds, Kristi; et al.
Abstract : Total medication burden (antihypertensive and nonantihypertensive medications) may be associated with poor systolic blood pressure (SBP) control. We investigated the association of baseline medication burden and clinical outcomes and whether the effect of the SBP intervention varied according to baseline medication burden in SPRINT (Systolic Blood Pressure Intervention Trial). Participants were randomized to intensive or standard SBP goal (below 120 or 140 mm Hg, respectively); n=3769 participants with high baseline medication burden (≥5 medications) and n=5592 with low burden (<5 medications). Primary outcome: differences in SBP. Secondary outcomes: 8-item Morisky Medication Adherence Scale and modified Treatment Satisfaction Questionnaire for Medications measured at baseline and 12 months and incident cardiovascular disease events and serious adverse events throughout the trial. Participants in the intensive group with high versus low medication burden were less likely to achieve their SBP goal at 12 months (risk ratio, 0.91; 95% CI, 0.85–0.97) but not in the standard group (risk ratio, 0.98; 95% CI, 0.93–1.03; P interaction <0.001). High medication burden was associated with increased cardiovascular disease events (hazard ratio, 1.39; 95% CI, 1.14–1.70) and serious adverse events (hazard ratio, 1.34; 95% CI, 1.24–1.45), but the effect of intensive versus standard treatment did not vary between medication burden groups ( P interaction >0.5). Medication burden had minimal association with adherence or satisfaction. High baseline medication burden was associated with worse intensive SBP control and higher rates of cardiovascular disease events and serious adverse events. The relative benefits and risks of intensive SBP goals were similar regardless of medication burden. Clinical Trial Registration—: URL: http://www.clinicaltrials.gov . Unique identifier: NCT01206062 Abstract : Supplemental Digital Content is available in the text.